From Strength to Strength : finding success, happiness, and deep purpose in the second half of life - Brooks, C. Arthur, ....- (Londen : Green Tree, 2023)
In the first half of life, ambitious strivers embrace a simple formula for success in work and life: focus single-mindedly, work tirelessly, sacrifice personally, and climb the ladder relentlessly. It works. Until it doesn't. The second half of life is governed by different rules. In middle age, many strivers begin to find success coming harder and harder, rewards less satisfying, and family relationships withering. In response, they do what strivers always do: they double down on work in an attempt to outrun decline and weakness, and deny the changes that are becoming more and more obvious. The result is often anger, fear, and disappointment at a time in life that they imagined would be full of joy, fulfilment and pride. It doesn't have to be that way. In From Strength to Strength, happiness expert and bestselling author Arthur C. Brooks reveals a path to beating the 'striver's curse.' Drawing on science, classical philosophy, theology and history, he shares strategies for releasing old habits and forming new life practices, showing you how to: - Kick the habits of workaholism, success addiction, and self-objectification - Meditate on death - in order to beat fear and live well - Start a spiritual adventure - Embrace weakness in a way that turns it into strength. Change in your life is inevitable, but suffering is not. From Strength to Strength shows you how to accept the gifts of the second half of life with grace, joy, and ever deepening purpose.
Keywords: Levenskunst